Agrobiodiversity and plant use categories in coffee-based agroforestry in East Java, Indonesia - IRMA ARDI KUSUMAWATI; MILA OKTAVIA MARDIANI; EKA PURNAMASARI; JATI BATORO; MEINE VAN NOORDWIJK; KURNIATUN HAIRIAH (Society for Indonesian Biodiversity, 2022)
Abstract. Kusumawati IA, Mardiani MO, Purnamasari E, Batoro J, van Noordwijk M, Hairiah K. 2022. Agrobiodiversity and plant use categories in coffee-based agroforestry in East Java, Indonesia. Biodiversitas 23: 5412-5422. Beyond documenting the ethnobotanical knowledge by managers of complex agroforestry systems, the actual use of such knowledge in adapting to new circumstances and adopting new practices in dynamic farming systems has been described as ecological wisdom. Our study in the Kali Konto catchment of East Java (Indonesia) focused on an inventory of plants that are part of coffee-based agroforestry, their various types of use, and the role they play in the further integration of livestock into the local farming system. The 48 respondents mentioned, on average, 105 combinations of plant species and use categories for their coffee agroforestry plots. Across nine use categories (food, with spices and food wrapping as subcategories, animal fodder, medicine, construction, hedge/ornamentals, handicrafts, ritual uses), a total of 83 plant species (in 36 botanical plant families) were mentioned, with on average 2.18 reported uses per species. A small majority (56%) of the plant species was actively managed (and often planted); the rest were spontaneously established species.